Characterization of particulate matters and total VOC emissions from a binder jetting 3D printer - Afshar-Mohajer, Nima; Wu, Chang-Yu; Ladun, Thomas; Rajon, Didier A.; Huang, Yong (Building and environment, 2015)
Binder jetting 3D printing is a popular type of additive manufacturing and a powerful tool for creating parts and prototypes. Due to continuous movement of dry powders inside printer chambers and injection of resin-like binder fluid during printing, binder jetting 3D printers are a potential emission source of fine particulate matters (PM) and volatile organic compounds (VOCs). In this study, real-time measurements of total VOC (TVOCs) and aerosol (10 nm–10 μm) during a 2-h continuous operation of a binder jetting printer were incorporated into a time-varying mass balance model to obtain the emission rates. The particle sizes between 205 and 407 nm had the highest emission rates by count. Time weighted average PM2.5 and PM10 and TVOC over a 24-h period all exceeded the USEPA ambient air quality standards. Continuous operation of the 3D printer led to a PM2.5 level 10 times greater than the standard (344 vs 35 μg/m3) and a PM10 level 3 times higher than the standard (474 vs 150 μg/m3). TVOC concentrations with a maximum value of 1725 μg/m3 exceeded upper limit concentrations recommended by the Environment Institute of European Commission, and USGBC-LEED. Ultrafine particles emitted from the binder jetting 3D printer were 104–105 times lower than those from typical fused deposition modeling (FDM) type of 3D printers using polylactic acid (PLA), but production of particles larger than 200 nm was significantly higher. The results suggest installing binder jetting 3D printers in an enclosure with proper ventilation for reducing the health risks. •The highest PM and TVOC emissions observed when the printed object was ejected.•The particle sizes between 205 and 407 nm had the highest emission rates by count.•TVOC emission rate exceeded the recommended values throughout the printing process.•UFPs emission rates from the device were upto 105 times lower than FDM 3D printers.•Emission of supermicron particles is more than other types of 3D printers.